Tanggapan Siswa Terhadap Penggunaan Model Pembelajaran Tematik Integratif Hubungannya Dengan Motivasi Belajar Mereka Dalam Pelajaran PAI - Cantika Riani; Cecep Anwar; Irfan Ahmad Zain (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to determine: 1) The reality of student responses to the use of thematic integrative learning models, 2) The reality of student learning motivation in PAI subjects. 3) The reality of the relationship between students' responses to the use of integrative thematic learning models and students' learning motivation. Through a quantitative approach and descriptive correlation method. Data collection techniques are; interviews, observations, questionnaires, and document studies. Data analysis was carried out with a logical approach for qualitative data and a statistical approach for quantitative data. With partial analysis of indicators and correlation analysis. Based on the results of data analysis, it was concluded that: 1) The reality of student responses to the use of the integrative thematic learning model was categorized as positive with an average value of 3.89. 2) The reality of student learning motivation in PAI subjects is in the high category with an average value of 3.9. 3) The relationship between students' responses to the use of the thematic integrative learning model (X) and students' learning motivation in PAI lessons (Y) belongs to the category of positive and significant correlation. With the Spearman rank correlation test, the results obtained are 0.06 which is in the interval 0.00 0.99 which means that it is categorized into a positive correlation. The correlation used follows the linear regression equation model Y= 41.11+0.27. Based on the equation, it can be seen that the (+) sign indicates an increase in students' learning motivation in line with the increase in students' positive responses to the integrative thematic learning model.